Genetic Variability of 15 Robusta Coffee Genotypes Selected by Farmer Based on SSRs Markers - Syafaruddin, Syafaruddin; Randriani, Enny; Dani, Dani; Sulistyorini, Indah; Pabendon, M. B. (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
Robusta coffee (Coffea canephora) has been grown widely in Indonesia, especially in Bengkulu Province. For the last few decades, some farmers have been selected and developed several Robusta clones through plagiotropic shoot grafting technique to replace earlier coffee populations which were derived from seed. Hence, it would reduce the genetic diversity of Robusta coffee at farmerâs field. To understand the genetic variability among 15 Robusta coffee genotypes selected by farmer, it is important to perform molecular analysis. Leaf samples of 15 Robusta coffee genotypes selected by farmer were collected from smallholder Robusta coffee plantations in Bengkulu Province. Genetic diversity analysis was conducted in the Germplasm, Breeding, and Biotechnology Laboratory of Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), and Molecular Biology Laboratory, Indonesian Cereals Research Institute (ICERI). DNA samples were amplified using 34 SSRs markers. The result showed that 23 out of 34 SSRs markers had high polymorphism levels. Allele number per locus ranged from 2-8 with an average of 4 alleles per locus. Dendrogram analysis based on genetic similarity was obtained with score of about 0,44-0,79, and r score = 0,92 (good fit). Based on cluster analysis as well as PCoA analysis, there are three distinct groups of genotypes. Those three groups can be distinguished by specific character of leaf morphotype. Nevertheless, the majority of genotypes were clustered together into the single group. This indicates narrow genetic diversity among Robusta genotypes that selected by farmer.Kopi Robusta telah dikembangkan secara luas di Indonesia, khususnya di Provinsi Bengkulu. Beberapa dekade terakhir sebagian petani telah menyeleksi dan mengembangkan beberapa genotipe dengan teknik sambung tunas plagiotrop untuk merehabilitasi populasi kopi Robusta asal biji. Oleh sebab itu, terdapat peluang terjadinya penurunan keragaman genetik kopi Robusta di lahan petani. Analisis molekuler perlu dilakukan untuk mengevaluasi keragaman genetik antar 15 genotipe kopi Robusta hasil seleksi petani. Kegiatan analisis keragaman genetik dilaksanakan di Laboratorium Plasma Nutfah, Pemuliaan, dan Bioteknologi, Balai Penelitian Tanaman Industri dan Penyegar (Balittri), Sukabumi dan Laboratorium Biologi Molekuler, Balai Penelitian Tanaman Serealia (Balitsereal), Maros. DNA diamplifikasi dengan menggunakan 34 marka SSR. Hasil penelitian menunjukkan bahwa 23 dari 34 marka SSR yang digunakan mampu menghasilkan tingkat polimorfisme yang tinggi. Jumlah alel berada pada kisaran 2-8 alel per lokus dengan rata-rata 4 alel per lokus SSR. Analisis dendrogram berdasarkan kemiripan genetik diperoleh dengan skor sekitar 0,44-0,79 dan skor r = 0,92 (good fit). Berdasarkan hasil analisis gerombol dan analisis komponen utama diketahui bahwa terdapat tiga kelompok genotipe. Masing-masing kelompok dapat dibedakan berdasarkan karakter morfotipe daun. Meskipun demikian, sebagian besar genotipe diklasifikasikan ke dalam satu kelompok. Ini menandakan bahwa keragaman genetik klon-klon kopi Robusta hasil seleksi petani cenderung rendah.Keywords: Coffea canephora, klon plagiotropik, kehilangan genetik